LRP5 regulates cardiomyocyte proliferation and neonatal heart regeneration by the AKT/P21 pathway. Issue 10 (16th April 2022) - Zhou, Huixing; Zhang, Fulei; Wu, Yahan; Liu, Hongyu; Duan, Ran; Liu, Yuanyuan; Wang, Yan; He, Xiaoyu; Zhang, Yuemei; Ma, Xiue; Guan, Yi; Liu, Yi; et al.
Abstract: The neonatal heart can efficiently regenerate within a short period after birth, whereas the adult mammalian heart has extremely limited capacity to regenerate. The molecular mechanisms underlying neonatal heart regeneration remain elusive. Here, we revealed that as a coreceptor of Wnt signalling, low‐density lipoprotein receptor‐related protein 5 (LRP5) is required for neonatal heart regeneration by regulating cardiomyocyte proliferation. The expression of LRP5 in the mouse heart gradually decreased after birth, consistent with the time window during which cardiomyocytes withdrew from the cell cycle. LRP5 downregulation reduced the proliferation of neonatal cardiomyocytes, while LRP5 overexpression promoted cardiomyocyte proliferation. The cardiac‐specific deletion of Lrp5 disrupted myocardial regeneration after injury, exhibiting extensive fibrotic scars and cardiac dysfunction. Mechanistically, the decreased heart regeneration ability induced by LRP5 deficiency was mainly due to reduced cardiomyocyte proliferation. Further study identified AKT/P21 signalling as the key pathway accounting for the regulation of cardiomyocyte proliferation mediated by LRP5. LRP5 downregulation accelerated the degradation of AKT, leading to increased expression of the cyclin‐dependent kinase inhibitor P21. Our study revealed that LRP5 is necessary for cardiomyocyte proliferation and neonatal heart regeneration, providing a potential strategy to repair myocardial injury.